Structural and Molecular Conservation of Glucagon-Like Peptide-1 and Its Receptor Confers Selective Ligand-Receptor Interaction - Moon, Mi Jin; Kim, Dong-Kyu; Cho, Eun Bee; Hwang, Jong-Ik; Vaudry, Hubert; Seong, Jae Young (Frontiers in Endocrinology, 2012)
Glucagon like peptide-1 (GLP-1) is a major player in the regulation of glucose homeostasis. It acts on pancreatic beta cells to stimulate insulin secretion and on the brain to inhibit appetite. Thus, it may be a promising therapeutic agent for the treatment of type 2 diabetes mellitus and obesity. Despite the physiological and clinical importance of GLP-1, molecular interaction with the GLP-1 receptor (GLP1R) is not well understood. Particularly, the specific amino acid residues within the transmembrane helices and extracellular loops of the receptor that may confer ligand-induced receptor activation have been poorly investigated. Amino acid sequence comparisons of GLP-1 and GLP1R with their orthologs and paralogs in vertebrates, combined with biochemical approaches, are useful to determine which amino acid residues in the peptide and the receptor confer selective ligand-receptor interaction. This article reviews how the molecular evolution of GLP-1 and GLP1R contributes to the selective interaction between this ligand-receptor pair, providing critical clues for the development of potent agonists for the treatment of diabetes mellitus and obesity.